Kompetensi Perkembangan Oosit Kambing Kacang dengan Diameter Berbeda pada Medium yang Disuplementasi Cairan Folikel (DEVELOPMENTAL COMPETENCE OF KACANG GOAT OOCYTES WITH DIFFERENT DIAMETER ON MEDIUM WITH FOLLICULAR FLUID SUPPLEMENTATION) - Harris, Ali; Rahayu, Sri; Ciptadi, Gatot (Jurnal Veteriner; Vol 16 No 2 (2015), 2015)
The purpose of this study was to determine the developmental competence of local goats oocytes on thebasis of their diameter in the medium supplemented with follicular fluid. Ovaries obtained fromSlaughterhouse, Malang City were collected and washed with NaCl containing streptomycin and penicillinat 32-35oC. Oocytes were obtained by follicular aspiration using a 10 ml syringe and needle 18 G needle.Oocytes were then divided into 3 groups on based at their diameter, group 1 (<160,5 ?m), group 2 (160,5-170,0?m) and group 3 (> 170,0?m). Follicular fluid was obtained by pooling the goat follicular fluid fromfollicles which have 3-8 mm in diameter. Maturation medium used was TCM-199 + 10% follicularfluid.Oocytes matured for 26 hours at 39oC and 5% CO2 with maximum humidity. Observation of oocytedevelopmental competence includes level cumulus cell expansion and maturation level of the nucleus. Theresults showed that the oocytes in groups 2 (160,5-170,0?m) and 3 (> 170,0?m) have a maximum ofcumulus expansion level 1 (63,8 and 74%) and metaphase II (56,6% and 68,5%).It is concluded that thediameter of oocytes had an influence on oocyte developmental competence (p <0,05), and can be consideredfor oocytes selection criteria.
Keywords: developmental competence, goat oocyte diameter, follicular fluid